Service Performance Reporting in New Zealand Charities - Ahmed, Hina (Auckland University of Technology, 2021)
This study investigates the service performance reports of registered Tier 3 and Tier 4 charities in New Zealand to identify the performance indicators disclosed according to the regulatory requirements. The research uses the content analysis index to examine the performance indicators reported by smaller charities of this size. To assess the impact of changes in reporting requirements, a comparison was made between reporting years of 2016 and 2019. It is observed that charities from both Tiers have furnished statements of service performance with a low level of compliance and are still in the phase of adopting the regulatory changes. Acknowledging the limitations of the study, this dissertation contributes to the understanding regarding the disclosures made in the statement of service performance for Tier 3 and Tier 4 and offers further research opportunities on performance disclosures made by small charities.
Keywords: Charities; Service Performance Reporting; NZ Charities; Charity Performance Indicators